2010
DOI: 10.1002/da.20705
|View full text |Cite
|
Sign up to set email alerts
|

Should an obsessive-compulsive spectrum grouping of disorders be included in DSM-V?

Abstract: The obsessive-compulsive (OC) spectrum has been discussed in the literature for two decades. Proponents of this concept propose that certain disorders characterized by repetitive thoughts and/or behaviors are related to obsessive-compulsive disorder (OCD), and suggest that such disorders be grouped together in the same category (i.e., grouping, or “chapter”) in DSM. This paper addresses this topic and presents options and preliminary recommendations to be considered for DSM-V. The paper builds upon and extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
163
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(176 citation statements)
references
References 374 publications
10
163
1
Order By: Relevance
“…Consequently, conditions from the strongly impulsive end of the spectrum, such as pathological gambling, sexual addiction, compulsive shopping, binge eating, and other impulsive disorders associated with pleasurable experiences, were excluded from further consideration. This decision found a middle ground between, on the one hand, those who were against any changes to the existing OCD classification [29] or who proposed a joint category of anxiety and obsessive-compulsive disorders [30] and, on the other, those who favored a broad transdiagnostic category of compulsive-impulsive disorders [21,24]. This decision was consistent with emerging genetic, familial and comorbidity studies showing that addictive disorders and eating disorders are likely not genetically related to OCD [12].…”
Section: Candidate Ocrdssupporting
confidence: 61%
See 1 more Smart Citation
“…Consequently, conditions from the strongly impulsive end of the spectrum, such as pathological gambling, sexual addiction, compulsive shopping, binge eating, and other impulsive disorders associated with pleasurable experiences, were excluded from further consideration. This decision found a middle ground between, on the one hand, those who were against any changes to the existing OCD classification [29] or who proposed a joint category of anxiety and obsessive-compulsive disorders [30] and, on the other, those who favored a broad transdiagnostic category of compulsive-impulsive disorders [21,24]. This decision was consistent with emerging genetic, familial and comorbidity studies showing that addictive disorders and eating disorders are likely not genetically related to OCD [12].…”
Section: Candidate Ocrdssupporting
confidence: 61%
“…Most respondents believed that a new category of OCD disorders should be small; thus, it should only include BDD (72%), trichotillomania (70%), tic disorders (61%) and hypochondriasis (57%). Fifty-five percent were against the inclusion of OCPD and the vast majority disapproved of the inclusion of impulse control disorders other than trichotillomania (67% ), eating disorders (72%), autism (91%), and addictions (95%) [30,31].…”
Section: Candidate Ocrdsmentioning
confidence: 99%
“…imipramine Clomipramine Collaborative Study Group, 1991;Greist et al, 1995Greist et al, 1920Greist et al, 1950 Stein & Hollander, 1993;Hollander et al, 2007 Figure 1 PG KM Holden, 2001OCSD Stein & Hollander, 1993Hollander et al, 2007; 2011 Hollander et al, 2007;OCSD DSM-5 Hollander et al, 2007Phillips et al, 2010;Hollander et al, 2007Phillips et al, 2010; 2011 Figure 2 OCSD comorbidity Schwartz et al, 2003;2004;Menzies et al, 2007;Stein, 2008;Milad & Rauch, 2012BDD Stein, 2008Phillips et al, 2010;Veale & Matsunaga, 2014 OCD OCSD, (Freud, S. (1926). Hemmung, symptom, und angst. …”
Section: CMImentioning
confidence: 99%
“…Indeed it has been suggested that the evidence for the construct validity of these two scales was mixed (Phillips et al, 2010). However, where OCD can be defined as a mental disorder characterized by ego-dystonic, intrusive and time-consuming obsessions and compulsions, OCPD rather reflects an ego-syntonic personality style including stable traits such as perfectionism and rigidity.…”
Section: Obsessive-compulsivementioning
confidence: 99%